Impact of Methanol Photomediated Surface Defects on Photocatalytic H2 Production Over Pt/TiO2. Issue 2 (19th February 2020) - Jiang, Zhi; Qi, Rongjie; Huang, Zhengwen; Shangguan, Wenfeng; Wong, Roong Jien; Lee, Adam
Abstract : Co‐catalysts play a critical role in enhancing the efficiency of inorganic semiconductor photocatalysts; however, synthetic approaches to tailoring co‐catalyst properties are rarely the focus of research efforts. A photomediated route to control the dispersion and oxidation state of a platinum (Pt) co‐catalyst through defect generation in the P25 titania photocatalyst substrate is reported. Titania photoirradiation in the presence of methanol induces long‐lived surface defects which subsequently promote the photodeposition of highly dispersed (2.2 ± 0.8 nm) and heavily reduced Pt nanoparticles on exposure to H2 PtCl6 . The optimal methanol concentration of 20 vol% produces the highest density of metallic Pt nanoparticles. Photocatalytic activity for water splitting and associated hydrogen (H2 ) production under UV irradiation mirrors the methanol concentration employed during the P25 photoirradiation pretreatment, and resulting Pt loading, resulting in a common mass‐normalized H2 productivity of 3800 ± 130 mmol gPt −1  h −1 . Photomediated surface defects (arising in the presence of a methanol hole scavenger) provide electron traps that regulate subsequent photodeposition of a Pt co‐catalyst over P25, offering a facile route to tune photocatalytic efficiency. Abstract : Methanol‐induced photoactivation of P25 titania generates Ti 3+ defects that promote the subsequent photodeposition of highly dispersed Pt metal nanoparticle co‐catalyst over the semiconductor support, thereby enhancing photocatalytic H2 production from water.